Pengaruh Pendekatan Jelajah Alam Sekitar terhadap Sikap Peduli Lingkungan Siswa Sekolah Dasar - Siti Umi Hani; Muh. Idham Haliq; Dirga Ayu Lestari (Journal on Education, 2022)
This research aims to determine the effect of the environmental exploration approach on elementary school students' environmental care attitudes. This research uses the pretest and posttest control group design method. This research takes the form of a true experimental study. The population in this study were all fourth grade students. Samples were taken using a purposive sampling technique, so that class IVA was obtained as an experimental class with the JAS approach and IV B as a control class was given learning using the caramah method. Data collection using questionnaires. The results of the average environmental care attitude score for the experimental class before learning were not much different from the average score for the control class, namely 51.85 and 50.46. After the learning was carried out, the average attitude of caring for the environment in the experimental class was 53.58. Meanwhile, the average post test for the control class was 53.19. Based on this, the natural exploration approach (JAS) can be applied to social studies learning because by learning to explore the natural surroundings students become active in the learning they gain in understanding things in their environment.